Medical graduates’ preparedness to practice: a comparison of undergraduate medical school training - Miles, Susan; Kellett, Joanne; Leinster, Sam J. (BMC medical education, 2017)
Background There is evidence that newly qualified doctors do not feel prepared to start work. This study examined views of first year Foundation doctors (F1s) regarding how prepared they felt by their undergraduate medical education for skills required during the first Foundation training year in relation to their type of training. Method One-hundred and eighty two F1s completed a questionnaire during their first rotation of Foundation training. Analysis was conducted by type of medical school training: Problem-Based Learning (PBL), Traditional or Reformed. Results F1s from medical schools with a PBL curriculum felt better prepared for tasks associated with communication and team working, and paperwork than graduates from the other medical school types; but the majority of F1s from all three groups felt well prepared for most areas of practice. Less than half of graduates in all three groups felt well prepared to deal with a patient with neurological/visual problems; write referral letters; understand drug interactions; manage pain; and cope with uncertainty. F1s also indicated that lack of induction or support on starting work was affecting their ability to work in some areas. Conclusions Whilst F1s from medical schools with a PBL curriculum did feel better prepared in multiple areas compared to graduates from the other medical school types, specific areas of unpreparedness related to undergraduate and postgraduate medical training were identified across all F1s. These areas need attention to ensure F1s are optimally prepared for starting work.